Epidemiology of Hepatocellular Carcinoma and Intrahepatic Cholangiocarcinoma - Massarweh, Nader N. (Cancer Control, 2017)
Hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC) are the most frequently occurring types of primary liver cancer and together are among the most common incident cancers worldwide. There are a number of modifiable and nonmodifiable HCC and ICC risk factors that have been reported. A review of the existing literature the epidemiology and risk factors for HCC and ICC was performed. There are a number of major infectious, lifestyle, metabolic, and heritable risk factors for both HCC and ICC. Some of these risk factors are either potentially preventable (eg, alcohol and tobacco use) or are currently treatable (eg hepatitis infection). In most cases, the molecular pathway or mechanism by which these etiologic factors cause primary liver cancer has not been well delineated. However, in nearly all cases, it is believed that a given risk factor causes liver injury and inflammation which results in chronic liver disease. Given the rising prevalence of several common HCC and ICC risk factors in the western world, the best opportunities for improving the care of these patients are either through the prevention of modifiable risk factors that are associated with the development of chronic liver disease or the identification of at risk patients, ensuring they are appropriately screened for the development of primary liver cancer, and initiating treatment early.